1975
DOI: 10.2466/pms.1975.41.3.931
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic Ear Preferences of Stuttering Children and Adults

Abstract: 39 stutterers and 39 normal speakers indicated their ear preferences for dichotically presented words and digits. A single response mode for both dichotic words and digits was selected to study speech perception. Stutterers showed significantly less of the normal right-ear preference for dichotic words and digits than non-stutterers. The proportion of stutterers who failed to demonstrate a right-ear preference for dichotic words was significantly greater than for non-stutterers. 18% of the stutterers and none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…A few years later, data obtained from other dichotic listening experiments, e.g., Sommers, Brady, & Moore (1975), showed a large percentage of stutterers to exhibit a reversal of the typical right ear preference. The investigators stated that ".…”
Section: Ear Preferencementioning
confidence: 96%
“…A few years later, data obtained from other dichotic listening experiments, e.g., Sommers, Brady, & Moore (1975), showed a large percentage of stutterers to exhibit a reversal of the typical right ear preference. The investigators stated that ".…”
Section: Ear Preferencementioning
confidence: 96%
“…A range of behavioural methods have been used to infer hemispheric activity in people who stutter in response to auditory and visual stimuli; for example, dichotic listening (Blood, 1985;Curry & Gregory, 1969;Rosenfield & Goodglass, 1980;Sommers, Brady, & Moore, 1975; see Code, 1998a, for review) and tachistoscopic viewing (Hand & Haynes, 1983;Moore, 1976;Szelag, Garwarska-Kolek, Herman, & Stasiek, 1993). More recently a range of neural imaging studies have been conducted using Positron Emission Tomography (PET), Single-Positron Emission Computerised Tomography (SPECT), and Functional Magnetic Resonance Imaging (fMRI) to examine activation in the brains of people who stutter (Ingham, 2001;Ingham et al, 1996;Ingham, Ingham, Finn, & Fox, 2003;Pool, Devous, Freeman, Watson, & Finitzo, 1991;Watson, Freeman, Devous, Chapman, Finitzo, & Pool, 1994).…”
mentioning
confidence: 99%
“…Stut terers demonstrated their largest ear prefer ence on the two-syllable word test and the rhyming word task and it was a left ear pref erence. Sommers et al [1975] compared three dif ferent age-groups of children and adult non stutterers and stutterers on word pairs and digit pairs presented dichoticallv. They found that stutterers showed significantly less of the normal right ear preference for dichotic words and digits than the nonstutterers.…”
Section: Auditory Processes In Stutterersmentioning
confidence: 99%